War and captivity in the New Kingdom of Granada, 16th and 17th centuries - Montoya Guzmán, Juan David; Arango Puerta, Mauricio (Cuadernos de Historia Moderna, 2025)
The aim of this article is to analyze captivity as a practice that impacted the different groups that constituted the society of the New Kingdom of Granada during the early Modern Age. Although Colombian historiography has focused on studying Africans who were enslaved and deported to work mainly in gold mines, there is less knowledge about the numerous indigenous nations that were dehumanized to work on estates and in the houses of European conquistadors. The captivity of natives was complemented by that of Spaniards, who were captured on the roads, taken out of cities, or seized during armed conflicts in frontier territories. Thus, based on a review of a broad documentary corpus, following life itineraries and quantitative information, the goal is to understand captivity in America as a common and widespread political practice carried out by conflicting factions across various areas of the Hispanic Monarchy.
Keywords: captivity; Indians; Spaniards; borders; New Kingdom of Granada; Hispanic Monarchy